Pricing Carbon - Moritz A. Drupp; Frikk Nesje; Robert C. Schmidt (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the variation of global and unilateral carbon price recommendations and their determinants. To this end, we provide survey evidence on carbon pricing from more than 400 experts across almost 40 countries. We quantify the extent of (dis-)agreement and reveal that a majority of experts can agree on some short- and medium-term global carbon price levels, and on unilateral carbon price levels in most countries. We find little evidence for free-riding. Indeed, experts' unilateral carbon price recommendations with border carbon adjustment are, on average, higher than global recommendations. Furthermore, border carbon adjustment facilitates higher price recommendations and tends to foster agreement among experts on carbon price levels. We analyze how experts' recommendations vary with additional survey data on key policy design issues, such as instrument choice, other likely determinants of carbon price recommendations as well as country characteristics and observable expert characteristics.
Keywords: Q54; H43; 330; carbon pricing; expert survey; carbon tax; emission trading; border carbon adjustment; climate policy